FireProtDB 2.0: large-scale manually curated database of the protein stability data - Musil, Milos; Borko, Simeon; Planas-Iglesias, Joan; Lacko, David; Rosinska, Monika; Kabourek, Petr; Martins, Lígia O; Tataruch, Mateusz; Damborsky, Jiri; Mazurenko, Stanislav; Bednar, David (Nucleic acids research, 2026)
Thermostable proteins are crucial in numerous biomedical and biotechnological applications. However, naturally occurring proteins have evolved to function in mild conditions, and laboratory experiments aiming at improving protein stability have proven laborious and expensive. Computational methods overcome this issue by providing a cheap and scalable alternative. Despite significant progress, their reliability is still hindered by the availability of high-quality data. FireProtDB 2.0 (http://loschmidt.chemi.muni.cz/fireprotdb) is a large-scale database aggregating stability data from multiple sources. The second version builds upon its predecessor, retaining its original functionality while introducing a new approach to data storage and maintenance. The new scheme enables the introduction of both absolute and relative data types connected with measurements of wild-types, mutants, protein domains, and de novo designed proteins. Furthermore, while the original database was limited to single-point mutations, more complex data such as insertions, deletions, and multiple-point mutations are now available. As a result, the inclusion of large-scale mutagenesis has increased the size of the database from 16 000 to almost 5 500 000 experiments. Moreover, the updated abstract scheme is fully expandable with any new measurements and annotations without the need for any restructuring. Finally, the tracking of history together with fixed identifiers is in accordance with the FAIR principles.
Keywords: internet; stabilita proteinů; Data Curation; výpočetní biologie; Software; databáze proteinů; software; Proteins; Computational Biology; proteiny; Internet; datové kurátorství; Protein Stability; Databases, Protein